2020
DOI: 10.2147/jpr.s259994
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Long-Term Outcome of CT-Guided Pulsed Radiofrequency in the Treatment of Idiopathic Glossopharyngeal Neuralgia: A Retrospective Multi-Center Case Series</p>

Abstract: Background: Safer and minimal invasive treatment options with minor side effects are in great demand in the treatment of glossopharyngeal neuralgia (GPN). Pulsed radiofrequency (PRF) is a micro-destructive procedure that could be applied repeatedly without irreversible damage to target tissue. However, few studies have reported the long-term clinical outcomes of PRF in the management of idiopathic GPN patients. Methods: We retrospectively investigated the efficacy and safety of computed tomography (CT)-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“… 16 , 24 Another study conducted by Jia et al demonstrated that PRF could provide early pain relief with an efficacy rate of 93.3%. 25 Overall, these studies concluded that minimally invasive treatments such as RFT, and PRF are effective in reducing GPN-related pain. However, these treatments can have adverse effects, such as hoarseness and difficulties with drinking and swallowing.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 16 , 24 Another study conducted by Jia et al demonstrated that PRF could provide early pain relief with an efficacy rate of 93.3%. 25 Overall, these studies concluded that minimally invasive treatments such as RFT, and PRF are effective in reducing GPN-related pain. However, these treatments can have adverse effects, such as hoarseness and difficulties with drinking and swallowing.…”
Section: Discussionmentioning
confidence: 95%
“…However, no similar findings were observed in the other two retrospective studies on PRF and RFT treatment of GPN. 16 , 25 Hence, this speculation requires confirmation through larger prospective research samples.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that over the long term, pulsed radiofrequency is an efficient and safe treatment option for those afflicted with GPN. 35 Because of the success of pulsed radiofrequency in reducing the painful symptoms of GPN, some researchers wanted to see if performing the same minimally invasive procedure would have a similar outcome in patients with oropharyngeal carcinoma who were experiencing neuralgia due to the same glossopharyngeal nerve. The study looked at 25 patients with oropharyngeal carcinoma and for more than 3 months, the PRF provided a significant reduction in pain and improvement in sleep in 23 of the patients (92%).…”
Section: Minimally-invasive Optionsmentioning
confidence: 99%
“…A nerve block is performed via the lateral cervical approach [ 7 ]. Meanwhile, surgical treatment approaches for GPN include pulsed radiofrequency [ 8 ], percutaneous radiofrequency thermocoagulation(PRT) [ 9 ], microvascular decompression(MVD) [ 10 ], and stereotactic body radiation therapy [ 11 ]. These treatments aim to relieve pain and improve patients’ sleep and quality of life.…”
Section: Introductionmentioning
confidence: 99%